Look both ways : a tale told in ten blocks - Reynolds, Jason; Nabaum, Alexander (New York : Atheneum/Caitlyn Dlouhy Books, 2019)
"A collection of ten short stories that all take place in the same day about kids walking home from school"--
Keywords: Interpersonal relations -- Fiction; Schools -- Fiction